Boron Nitride Nanomaterials for Thermal Management Applications. Issue 7 (4th February 2015) - Meziani, Mohammed J.; Song, Wei‐Li; Wang, Ping; Lu, Fushen; Hou, Zhiling; Anderson, Ankoma; Maimaiti, Halidan; Sun, Ya‐Ping
Abstract Hexagonal boron nitride nanosheets (BNNs) are analogous to their two‐dimensional carbon counterparts in many materials properties, in particular, ultrahigh thermal conductivity, but also offer some unique attributes, including being electrically insulating, high thermal stability, chemical and oxidation resistance, low color, and high mechanical strength. Significant recent advances in the production of BNNs, understanding of their properties, and the development of polymeric nanocomposites with BNNs for thermally conductive yet electrically insulating materials and systems are highlighted herein. Major opportunities and challenges for further studies in this rapidly advancing field are also discussed.